The adventures of Alexander Barclay, Mountain Man: A narrative of his career, 1810 - 1855; His memorandom diary, 1845 - 1850 - Hammond, George P. frey50 (Fred A. Rosenstock, Old West Publishing Co. Denver, CO, 1976)
Englishman Alexander Barclay worked as a London corsetier, a pioneer farmer in Canada, a bookkeeper in St. Louis, was Superintendent of Bent's Fort, a fur trader and mountain man in Colorado and New Mexico, and built Barclay's Fort on the Santa Fe Trail in 1848. His life in North America is that of an adventurous man in the time of the untamed west.
Located in basement. Ask staff for retrieval.
Keywords: Frontier and pioneer life - History -- Traders - Colorado - New Mexico -- United States - Exploration -- Fortification; Biography